ANALISIS EKONOMI SYARIAH MENURUT SUDUT PANDANG AGAMA BUDDHA - Tulas Maitriya (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2021)
Sharia economics is a teaching that puts forward religious and ethical values in muamalah, which provides a fair value of benefits to both parties concerned and distributes existing losses so that they are not burdened with only one party. On this basis, this study was made to find out the correlation between Islamic economics and economics in Buddhism. The research method is based on literature review and uses methods that are relevant to existing theories. Sources of data used in this study took primary and secondary sources. Primary sources are Al-Quran and Hadith, Tipitaka. Secondary sources are popular books and other supporting sources that are relevant to the problem being discussed. The data analysis technique used in the preparation of the thesis mostly uses a deductive way of drawing conclusions. Deductively, namely the collection of data from things that are general to things that are specific, as well as correlatives that have a reciprocal relationship with one another. In this research, it was found that there was a correlation between Economics in Islam and Buddhism, which was carried out with effort without harming oneself, others or other creatures. From the point of view of Buddhism, it shows that the economy that is carried out must go through the right and legitimate path, according to what is taught, namely by being guided by the noble eightfold path, namely right livelihood. Buddhist economics not only considers one's own happiness, but also considers others.